The spliceosome assembly factor GEMIN2 attenuates the effects of temperature on alternative splicing and circadian rhythms - Schlaen, Rubén Gustavo (2015)
The mechanisms by which poikilothermic organisms ensure that biological processes are robust to temperature changes are largely unknown. Temperature compensation, the ability of circadian rhythms to maintain a relatively constant period over the broad range of temperatures resulting from seasonal fluctuations in environmental conditions, is a defining property of circadian networks. Temperature affects the alternative splicing (AS) of several clock genes in fungi, plants, and flies, but the splicing factors that modulate these effects to ensure clock accuracy throughout the year remain to be identified. Here we show that GEMIN2, a spliceosomal small nuclear ribonucleoprotein assembly factor conserved from yeast to humans, modulates low temperature effects on a large subset of pre-mRNA splicing events. In particular, GEMIN2 controls the AS of several clock genes and attenuates the effects of temperature on the circadian period in Arabidopsis thaliana. We conclude that GEMIN2 is a key component of a posttranscriptional regulatory mechanism that ensures the appropriate acclimation of plants to daily and seasonal changes in temperature conditions.